Pfvr me ajudem... Cliquem na imagem para ver a pergunta
Anexos:
Soluções para a tarefa
Respondido por
1
f(x) = 3x^2 - 4x + 1
A) f ( -1 ) = (3 • -1 )^2 - 4 • -1 + 1
f ( -1 ) = 9 + 4 + 1
f ( -1 ) = 14
B) f ( 0 ) = ( 3 • 0 )^2 - 4 • 0 + 1
f ( 0 ) = 0 - 0 + 1
f ( 0 ) = 1
C) f ( 1 ) = ( 3 • 1 )^2 - 4 • 1 + 1
f ( 1 ) = 9 - 4 + 1
f ( 1 ) = 6
D) f ( 2 ) = ( 3 • 2 )^2 - 4 • 2 + 1
f ( 2 ) = 36 - 8 + 1
f ( 2 ) = 29
E) f ( 3 ) = ( 3 • 3)^2 - 4 • 3 + 1
f ( 3 ) = 81 - 12 + 1
f ( 3 ) = 70
Espero ter ajudado!
A) f ( -1 ) = (3 • -1 )^2 - 4 • -1 + 1
f ( -1 ) = 9 + 4 + 1
f ( -1 ) = 14
B) f ( 0 ) = ( 3 • 0 )^2 - 4 • 0 + 1
f ( 0 ) = 0 - 0 + 1
f ( 0 ) = 1
C) f ( 1 ) = ( 3 • 1 )^2 - 4 • 1 + 1
f ( 1 ) = 9 - 4 + 1
f ( 1 ) = 6
D) f ( 2 ) = ( 3 • 2 )^2 - 4 • 2 + 1
f ( 2 ) = 36 - 8 + 1
f ( 2 ) = 29
E) f ( 3 ) = ( 3 • 3)^2 - 4 • 3 + 1
f ( 3 ) = 81 - 12 + 1
f ( 3 ) = 70
Espero ter ajudado!
Perguntas interessantes
Matemática,
9 meses atrás
Matemática,
9 meses atrás
Química,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás